2006
DOI: 10.1177/000312240607100202
|View full text |Cite
|
Sign up to set email alerts
|

National Context, Religiosity, and Volunteering: Results from 53 Countries

Abstract: and Zimbabwe. 13 Expected probabilities of volunteering are calculated for married men with average age (42.7 years) and average educational level (5.4).14 Note that originally the church attendance variable was ordinal. So, be careful when interpreting the effect of a single day increase. We checked whether the positive effect of church attendance is less strong at the higher end of the scale. Indeed, we found evi-Delivered by Ingenta to :

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

24
390
10
9

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 382 publications
(449 citation statements)
references
References 42 publications
(87 reference statements)
24
390
10
9
Order By: Relevance
“…Immigrants have a significantly lower probability of working for the charity, which is in accord with the existing literature on social integration, showing that immigrants are at a higher risk of being socially excluded with respect to social and political participation in general (see, e.g., Tsakloglou and Papadopoulos, 2002). Conforming existing research on the relationship between religiosity and volunteering (see, e.g., Curtis et al, 2001;Ruiter and de Graaf, 2006), which suggests that church members are more likely to be involved in voluntary organizations than non-members, individuals belonging to a religious denomination show a higher probability of working voluntarily and spending money. Since religious organizations are among the dominant voluntary organizations in most European societies (Gaskin and Smith, 1995), this does not mean that religious involvement boosts volunteering in general.…”
Section: Aggregate Volunteeringsupporting
confidence: 85%
See 1 more Smart Citation
“…Immigrants have a significantly lower probability of working for the charity, which is in accord with the existing literature on social integration, showing that immigrants are at a higher risk of being socially excluded with respect to social and political participation in general (see, e.g., Tsakloglou and Papadopoulos, 2002). Conforming existing research on the relationship between religiosity and volunteering (see, e.g., Curtis et al, 2001;Ruiter and de Graaf, 2006), which suggests that church members are more likely to be involved in voluntary organizations than non-members, individuals belonging to a religious denomination show a higher probability of working voluntarily and spending money. Since religious organizations are among the dominant voluntary organizations in most European societies (Gaskin and Smith, 1995), this does not mean that religious involvement boosts volunteering in general.…”
Section: Aggregate Volunteeringsupporting
confidence: 85%
“…Church membership is found to not only increase an individual's involvement in religious organizations, but is positively correlated with participation in secular organizations as well. Ruiter and de Graaf (2006) explain this "spillover effect" by the fact that people who are already involved in religious volunteering are more likely to communicate with people who volunteer for non-religious organizations. Hence, corresponding to network theory, their chance to volunteer for secular organizations should be high as well.…”
Section: Disaggregate Volunteeringmentioning
confidence: 99%
“…Still, it is conceivable that churchgoers in secular societies, because they are part of more cohesive communities, will experience more peer pressure to volunteer in religious organizations, which again increases the odds that their religious voluntary actions spillover into non-religious volunteering. For the Netherlands, De Hart (2014) recently showed that there is indeed a strong spillover effect from religious into nonreligious volunteering, while Ruiter and De Graaf (2006), conducting a crossnational study into religion and volunteering, demonstrated that in secular societies religious people are more active in both religious and non-religious volunteering. This line of reasoning results in our first hypothesis: Over time the proportion of regular churchgoers who volunteer for non-religious organizations has increased in the Netherlands (H1).…”
Section: Changes In the Voluntary Behavior Of Dutch Churchgoersmentioning
confidence: 99%
“…In the Netherlands, this was shown by Bekkers and Schuyt (2008) and Van Tienen et al (2011). Why collective aspects of religion are particularly important in this respect is usually explained in terms of network theory (Bekkers 2004;Ruiter and De Graaf 2006). What matters is that religion brings people together in close-knit social networks in which engagement in voluntary work is a social norm to which religious people are supposed to conform.…”
Section: Changes In the Proportion Of Regular Churchgoers In The Dutcmentioning
confidence: 99%
See 1 more Smart Citation